2021
DOI: 10.15282/ijame.18.1.2021.11.0646
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Industry 4.0 Concept on the Levers of Lean Manufacturing Approach in Manufacturing Industries

Abstract: Industrial companies looking for permanent performance are facing challenges of reducing production costs, reducing customer delivery delays and improving their quality products, this lead them to improve their responsiveness and flexibility to meet the varying needs of customers. To cope with these constraints, several industrial companies have adopted the Lean Manufacturing (LM)  concept, based on the Toyota production system, to reduce wastage according to a methodical and structured approach that has given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…With 'I4.0 technologies enhancing the capability of lean tools', authors have followed two different approaches. Firstly, they propose how specific individual I4.0 technology can incarnate the Lean Manufacturing approach, such as big data to improve decision-making, continuous improvement, value addition, and waste reduction (Ghouat et al, 2021 and, IoT-enabled data analytics to enhance the decision support system (Abd , Cobots for lean automation (Rossi et al, 2020), Cloud Computing (CC) with ML to enhance the Kanban system and propose Cloud Kanban (Shahin et al, 2020), and integrated Lean Value Stream which integrates seven I4.0 technologies (Tortorella et al, 2020b). Secondly, the authors have identified how combining different I4.0 technologies can impact each lean tool's delivery performance (Pereira et al, 2019;Rosin et al, 2020;Saxby et al, 2020;Valamede et al, 2020).…”
Section: Bibliometric Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…With 'I4.0 technologies enhancing the capability of lean tools', authors have followed two different approaches. Firstly, they propose how specific individual I4.0 technology can incarnate the Lean Manufacturing approach, such as big data to improve decision-making, continuous improvement, value addition, and waste reduction (Ghouat et al, 2021 and, IoT-enabled data analytics to enhance the decision support system (Abd , Cobots for lean automation (Rossi et al, 2020), Cloud Computing (CC) with ML to enhance the Kanban system and propose Cloud Kanban (Shahin et al, 2020), and integrated Lean Value Stream which integrates seven I4.0 technologies (Tortorella et al, 2020b). Secondly, the authors have identified how combining different I4.0 technologies can impact each lean tool's delivery performance (Pereira et al, 2019;Rosin et al, 2020;Saxby et al, 2020;Valamede et al, 2020).…”
Section: Bibliometric Analysismentioning
confidence: 99%
“…d) I4.0 technologies enhance lean tools' capability. e) Big data improves decision-making, continuous improvement, value addition, and waste reduction (Ghouat et al, 2021 and. f) I4.0 enhances the lean tool's capability and concludes Total Productive Maintenance .…”
Section: Important Lessons Learnedmentioning
confidence: 99%
“…Studies conducted to understand lean and Industry 4.0’s interdependence suggest that a lean production system is a prerequisite for Industry 4.0 (Dombrowski & Richter, 2018). The interdependence between the two supports organisations to remain competitive and stay ahead on the business curve, more so in the case of MSMEs, where the barriers of entry for competition and availability of alternate technology are very high (Ghobakhloo & Fathi, 2019; Ghouat et al, 2021). Thus, systematic analysis and review of existing literature indicate that lean manufacturing and Industry 4.0 are not mutually exclusive and can be integrated seamlessly to manage operations successfully.…”
Section: Lean and Industry 40mentioning
confidence: 99%
“…The objective of this work is to assess the potential of Industry 4.0 technologies to support the LM approach by supplying it with real-time data [20,21], in a representative sample of companies established in Morocco, figure 2.…”
Section: Studies and Surveys Of Companies Established In Moroccomentioning
confidence: 99%